Development of Enrichment Book on Poetry Text Writing Oriented to Creative Thinking Skill with Divine Values - Tasrifah, Tasrifah; Subyantoro, Subyantoro; Haryadi, Haryadi (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
Enrichment book is a secondary handout used for a means of improving, enriching, and developing students’ knowledge and skills. Inappropriate and uninventive use of enrichment book can lead to less impressive learning process for the students. As a result, their knowledge, skill, creativity, and experience are relatively limited. This study was to develop a prototype of enrichment book on poetry text writing oriented to creative thinking skill with divine values. The design was Research and Development (R&D). The data were students’ and teachers’ need on enrichment book. The initial part of enrichment book prototype used a principle under presentation and graphics aspects, namely easiness. Meanwhile, the content part used some principles under aspects such as material, presentation, creative thinking skills and divine values, namely attractiveness, cohesiveness, novelty, and easiness. Then, the final part used two principles under presentation aspect, namely cohesiveness and easiness.